Prevalence of Hydatid Cysts Harboured in Bovine Slaughtered in Selected Abattoirs: A Case Study from Kaduna Metropolis, Nigeria - Dibal , Deborah Madi; Vantsawa , Anthony Philip (Advanced Research in Biological Science Vol. 1, 2023)
This chapter aimed to determine the prevalence, risk factors and viability of cystic hydatidosis in bovine slaughtered in four selected abattoirs within Kaduna metropolis. Hydatidosis is cystic parasitosis caused by a larval stage of Echinococcus granulosus with immense economic and public health significance. As to many other parasitic infections, the life cycle of Echinococcus infection is complex which requires two mammalian hosts (intermediate and definitive hosts) for the completion of its life cycle. A cross-sectional study was conducted to evaluate the prevalence, organ distribution and characteristics of hydatid cysts in cattle slaughtered at Kaduna Metropolis abattoir. A total of 160 cattle at slaughter point, that is 40 from each abattoir were randomly sampled and examined for the presence of the hydatid cysts. Out of the 160 cattle examined (40 from each abattoir), 21 (12.2 %) were found to harbor visible hydatid cysts. Significantly higher infection (p < 0.05) was detected in cattle with poor body conditions than animals with moderate and fat body condition score. Animals used were all adults. Cysts were found to be distributed in the lung, liver, kidney, spleen and heart as follows: 42.9%, 38.0%, 4.76%, 9.50% and 4.76% respectively. According to the study, hydatidosis is a serious condition affecting cattle in Kaduna and the surrounding areas. It may result in significant financial losses since affected animals lose weight and suffer organ damage.Out of 36 hydatid cysts examined, 17 (47.22%), 14 (38.88%) and 5 (13.88%) were found to be small, medium and large- sized respectively. Likewise, out of 36 cysts assessed, 18 (50%) were fertile, 4 (11.11%) sterile and 14 (38.8%) were calcified. Of the 18 fertile cysts subjected for viability test, 12 (27.7%) were viable while, 8(22.2%) were non-viable. Health workers should be empowered to enlighten the abattoirs operation on the claim of hydatidosis transmission. They should also increase inspection visits and monitoring of abattoirs activities to avoid illegal consumption of hydatid infected organs.Anti–helminthic drugs should be made available to the bovine farmers in order to eliminate the parasites.